PENGGUNAAN METODE COOPERATIVE LEARNING PADA MATA PELAJARAN AKIDAH AKHLAK UNTUK MENINGKATAN KECERDASAN INTERPERSONAL PESERTA DIDIK DI MAN 2 BANGGAI - Abdul Razak Sipada; Ika Ratih Sulistiani; Qurroti A’yun (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The.problem in this study aims to describe the use of the Cooperative Learning method in moral aqidah subjects at MAN 2 Banggai, and the improvement of students' interpersonal intelligence in aqidah morality subjects at MAN 2 Banggai. The method used in this research is Classroom Action Research (CAR). The data in this study are. Interpersonal Skills Questionnaire, observation sheets and interviews.The data sources in this study were students of class XI IPA who were at MAN 2 Banggai with a total of 21 people. The data were collected by means of observation, interviews and documenta tion. The results of the study show that learning on the subject of moral aqidah to improve the interpersonal intelligence of students at MAN 2 Banggai, is carried out and refers to 4 important components, namely planning, implementation, observation, and reflection. increasing the interpersonal intelligence of students in the subjects of aqidah morality, aqidah morality at MAN 2 Banggai. In general, there was a significant increase, it can be seen from the results after the action of cycle 1 and cycle 2 students who had interpersonal intelligence experienceda significant increase, namely the high category amounted to 8 people (38%), students who had moderate interpersonal intelligence amounted to 13 people (61%), and students who have low interpersonal intelligence are 0 people. Kata Kunci: Metode, Cooperative Learning, Interperspnal